DB-FUZZY: um novo método para buscas em bancos de dados - Queirós Neto, Antonio (Universidade Federal Rural do Semi-Árido, 2020)
Nowdays, systems stored data increases rapidly. It may have different purposes, however, the standard in software industry is to store the data in databases. The time to retrieve a specific piece of data from a database is directly related to the volume of data stored. In this way, datasets with a significant volume of data would take longer to retrieve a specific tuple than smaller datasets. This paper proposes a new a novel method for search in databases, called DB-Fuzzy. It uses fuzzy concepts to locate individual data. It takes a constant number of steps for each searching, independently of the database size. Comparisons with literature method shows the efficiency of the proposed method
Keywords: Banco de Dados; Otimização de Busca; Lógica Fuzzy; Database; Search Optimization; Fuzzy Logic; CIENCIAS EXATAS E DA TERRA::CIENCIA DA COMPUTACAO